(untitled) (Jurnal Bina Praja, 2025)
This study explores the dynamics of digital democracy in Sinjai Regency by examining the factors that shape public participation, particularly access to information, digital literacy, and technological infrastructure. This study used a qualitative method with a phenomenological approach; data were collected through in-depth interviews, observations, focus group discussions, and documentation involving citizens, youth, government officials, and local digital media practitioners. The findings reveal five dominant factors influencing digital democracy: (1) limited and unequal internet access across regions, particularly in rural areas; (2) low digital literacy which reduces the ability of citizens to filter accurate political information; (3) the strong role of young people as digital actors in political engagement; (4) government digital initiatives-though available-remain underutilized due to limited public capability and uneven dissemination; and (5) local digital media serving as an important intermediary in delivering political information. These factors collectively contribute to the low level of digital participation in Sinjai. The study proposes several solutions, including expanding internet infrastructure through cross-sector collaboration, strengthening community-based digital literacy training, enhancing government digital services, and establishing an independent body to oversee digital democracy implementation. The results highlight the need for inclusive policies that consider geographical and socio-economic disparities. This research contributes novelty by focusing on digital democracy gaps at the local scale and emphasizing community capacity as a key determinant in achieving inclusive digital participation.